The Copyright (International Conventions)(Amendment No.3)Order 1962 - Anonymous (Her Majesty's Stationery Office, 1962)
The Copyright (International Conventions)(Amendment No.3)Order 1962
ERAF: A6.SI.1962.1641
Keywords: international; copyright; statutory